A cross sectional study of bone and cartilage biomarkers: correlation with structural damage in rheumatoid arthritis. Issue 1 (1st January 2018) - Ben Achour, Wael; Bouaziz, Mouna; Mechri, Meriem; Zouari, Béchir; Bahlous, Afef; Abdelmoula, Leila; Laadhar, Lilia; Sellami, Maryam; Sahli, Hela; Cheour, Elhem
ABSTRACT: The aim of our study was to assess the relationship between bone and cartilage remodeling biomarkers and joint damage in Rheumatoid Arthritis (RA), and to detect whether they have the capacity to predict the progression of joint disease assessment by computed tomography (CT) erosion score. We analyzed 65 female patients with established RA in our Rheumatology Department. Serum levels of bone and cartilage markers were measured: osteocalcin (OC), N-propeptide of type I collagen (PINP), collagen type I and II, C-telopeptide (CTX I, CTX-II) and cartilage oligomeric matrix protein (COMP). Radiography of both wrist and MCP joints were available. Two expert-readers independently scored articular damage and progression using the High-resolution low dose CT scan in a blinded fashion. 65 female patients with established RA with a median age of 44 years were included. The median disease-duration was two years and the median (Disease activity score) DAS 28 score at 4.46 [2.65–7.36]. The percentage of patient with low disease activity was 13.8%, while 55.4 and 30.8% for those with moderate and high disease activity respectively. The resorption bone markers were high in active versus non-active RA. Wrist and MCP erosion scores were also associated with RA activity. Our study shows that biomarkers of bone and cartilage collagen breakdown were related to specific joint erosion in RA and could predict subsequent radiographic damage in RA. Further larger scale longitudinal studies maybe needed to confirm our data.